2012
DOI: 10.1071/bt12096
|View full text |Cite
|
Sign up to set email alerts
|

Galls from Calliandra brevipes BENTH (Fabaceae : Mimosoidae): evidence of apyrase activity contribution in a plant - insect interaction

Abstract: By western blots, cross-immunoreactivity with polyclonal anti-potato apyrase antibodies identified the Calliandra brevipes apyrase as a band of 75 kDa in the tissues of non-galled stem and leaves, and those of globose galls. The non-galled tissues hydrolysed either ATP, ADP, UDP, GTP or GDP. In globose galls, ADP, UDP and GDP hydrolysis were 1.7–5.1-fold higher than in non-galled tissues. ADP and UDP hydrolysis either from non-galled or globose gall tissues were 10–38% stimulated by 5 mM calcium, and drastical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Interestingly, this ectopapyrase appears to be the target of elicitor and suppressor molecules secreted by the fungus. Extracellular ATP and the ectoapyrases that hydrolyze eATP also appear to be a battleground between plants and insects during defense responses [ 100 , 101 , 102 ].…”
Section: Role Of Ca 2+ /Cam-activated Apyrase Imentioning
confidence: 99%
“…Interestingly, this ectopapyrase appears to be the target of elicitor and suppressor molecules secreted by the fungus. Extracellular ATP and the ectoapyrases that hydrolyze eATP also appear to be a battleground between plants and insects during defense responses [ 100 , 101 , 102 ].…”
Section: Role Of Ca 2+ /Cam-activated Apyrase Imentioning
confidence: 99%
“…A follow-up study revealed that a protein highly abundant in Hessian fly larval salivary glands, the nucleoside diphosphate kinase (NDK), was indeed injected into host tissues during feeding (137). Apyrase activity levels are also higher in Calliandra brevipes galls than in non-galled tissues, suggesting a key role for this early signaling disruptor (together with other molecules) in the plant reprogramming induced by plant-manipulating insects (35). Interestingly, PRXs have been detected in the salivary secretions of several insects and have been shown to be required for successful M. incognita development (38).…”
Section: Nematode and Galling-insect Effector Repertoiresmentioning
confidence: 99%
“…A clear mechanism for this response would be that the salivary apyrases dampen wound-released ATP to restrict the plant defense response. Furthermore, a higher catalytic activity of apyrases was detected in globose insect galls on Calliandra brevipes ( Detoni et al, 2012 ). Similar mechanisms for controlling extracellular ATP concentrations are observed in the interactions between animals and parasitic worms or blood sucking insects ( Valenzuela et al, 2001 ; Da’dara et al, 2014 ).…”
Section: Role Of Extracellular Atp As a Dampmentioning
confidence: 99%